Is Tax Volatility Priced by Lenders in the Syndicated Loan Market?. Issue 4 (8th August 2019) - Saavedra, Daniel
Abstract: In this study, I consider the effects of tax risk from tax volatility on the pricing of syndicated debt. Tax volatility is an interesting feature in that managers have some discretion over the risks they take with their tax strategies, which, however, are often harder to monitor for outsiders than risks related to other business activities. Framing my predictions based on the theoretical model developed by Merton [1974], I hypothesize and find that tax volatility is incrementally informative to other priced risks suggesting that tax risks per se are relevant to lenders. Moreover, I find that the results are stronger when the loan contract does not include performance pricing provisions or other restrictions, such as capital expenditure covenants, that protect lenders. This evidence adds to knowledge about the real effects of tax risk.